2015
DOI: 10.1093/sw/swv053
|View full text |Cite
|
Sign up to set email alerts
|

Living Up to the Code’s Exhortations? Social Workers’ Political Knowledge Sources, Expectations, and Behaviors

Abstract: The National Association of Social Workers' (NASW's) Code of Ethics urges social workers to engage in political action. However, little recent research has been conducted to examine whether social workers support this admonition and the extent to which they actually engage in politics. The authors gathered data from a survey of social workers in Austin, Texas, to address three questions. First, because keeping informed about government and political news is an important basis for action, the authors asked what… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Cross-national comparisons reveal that SWs in New Zealand tend to be more politically active than their counterparts in Australia, South Africa (Gray et al, 2002) and Hong Kong (Chui and Gray, 2004), and US SWs were found to be more politically active than their Swiss counterparts (Ostrander et al, 2021). Studies on voting, the most common form of VPP, indicate that the level among SWs was higher than that of the general public in the US (Felderhoff et al, 2016), Canada (Douglas, 2008), New Zealand, South Africa (Gray et al, 2002) and Hong Kong (Chui and Gray, 2004).…”
Section: Researching the Extentmentioning
confidence: 97%
“…Cross-national comparisons reveal that SWs in New Zealand tend to be more politically active than their counterparts in Australia, South Africa (Gray et al, 2002) and Hong Kong (Chui and Gray, 2004), and US SWs were found to be more politically active than their Swiss counterparts (Ostrander et al, 2021). Studies on voting, the most common form of VPP, indicate that the level among SWs was higher than that of the general public in the US (Felderhoff et al, 2016), Canada (Douglas, 2008), New Zealand, South Africa (Gray et al, 2002) and Hong Kong (Chui and Gray, 2004).…”
Section: Researching the Extentmentioning
confidence: 97%
“…Studies into social work and politics in the United States (U.S.) have typically centered around the rates and types of political participation among social work practitioners and social work students. In fact, the literature has identified that social workers are more politically active than the general population and tend to participate in political activities that require lower levels of political engagement, such as voting (Domanski, 1998;Ezell, 1993;Felderhoff et al, 2016;Hamilton & Fauri, 2001;Mary, 2001;Ritter, 2007;Rome & Hoechstetter, 2010;Wolk, 1981). However, there is a subset of political social work literature that has explored the political ideology and policy preference of social work practitioners and students.…”
Section: Political Ideology and Affiliation In Social Work Literaturementioning
confidence: 99%
“…Although several studies have used non-probability sampling to understand the political participation of social workers (Felderhoff, Hoefer, & Watson, 2015;Swank, 2012), most studies on this subject have used random sampling (Hamilton & Fauri, 2001), often of NASW members (Ezell, 1993;Parker & Sherraden, 1992;Ritter, 2008;Rome & Hoechstetter, 2010;Wolk, 1981). The MLSWS is a nonprobability sample.…”
Section: Samplementioning
confidence: 99%